The Effect of Shuttle Run Training on 100-Metre Sprint Speed Among Students - Alfito Dini Wicaksono; Ahmad Bahriyanto (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
Sprint speed in the 100-meter event is an important component of physical education; however, students often show inconsistent performance due to limited specific training. This study aimed to determine the effect of shuttle run training on students’ sprint speed. An experimental method with a one-group pretest–posttest design was used involving 32 students of class X.8 at SMAN 1 Arjasa. Data were collected using a 100-meter sprint test and analyzed using a paired sample t-test. The results showed a significant improvement, with the average time decreasing from 15.58 seconds to 14.73 seconds (p < 0.05). The results of the analysis showed an increase in 100-metre sprint running speed after the shuttle run training. The average time decreased from 15.58 seconds in the pretest to 14.73 seconds in the posttest. The paired sample t-test showed a p-value < 0.001, indicating a significant difference between the results before and after treatment. Shuttle run training has been proven effective in improving students' 100-metre sprint speed. The application of this training can be a practical and efficient alternative in physical education in secondary schools. It can be concluded that shuttle run training is effective in improving students’ sprint speed and can be applied as a practical training method in physical education